Participation, worker’s control and self - management - Miloud SEFFARI (Revue des Sciences Humaines, 1998)
Participation of the workers in management is one of the issues that has been extensively discussed in industrialized countries. Many experiments on participation have been acheived throughtout the century. Participation is currently at the heart of interest and discussions in these countries. Suprisingly despite this importance it is almost unknown in the third world, espessially in Arab countries which gives the present article a particular importance. I hope readers and researchers in these contries will find in it a source of information about this topic. The article puts a particular emphasis on the conceptual discussion of the terms of participation, workers’ control and self-management, and shows that these concepts present also differences in methods and scope of research. Experiments on workers’ participation which have been successively carried out since the turn of the century, show the extent of the generalization of industrial democracy and the effeciency of participation in solving many of the problems faced by the entreprises in acheiving their tasks. Finally the article analyses the idea of those opposing workers participation and the excuses they advance in refusing this type of workers-management relations.